From EFL to ESL context: the impact of sociocultural environment on teachers’ professional identity development - Aljuhaish, Sultan Fahd; Fatiha Senom; Juliana Othman (Penerbit Universiti Kebangsaan Malaysia, 2020)
Teachers, like other professionals, are sometimes bound to change places of living, particularly when such a change takes the teachers to an entirely different country with a distinctive culture. This paper aims to trace three Saudi EFL (English as a Foreign Language) teachers who moved from Riyadh (Saudi Arabia) to Kuala Lumpur (Malaysia) to pursue their professional careers further. The main objective of the paper is to examine how the sociocultural context influences the professional identity formation of EFL teachers. The data of the study were collected through classroom observations and in-depth interviews that were then analyzed thematically. Findings of the study led to the emergence of four distinctive themes that include language-related identity, context-related identity, practiced and responsive teaching skills, and membership in Communities of Practice. Findings underscore the dynamic nature of language teacher identities as participants find themselves in different English language teaching contexts. Additionally, the findings highlight the important role of professional settings in supporting teachers’ professional identity development.